If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(2 + -1x) = x (2 * 2x + -1x * 2x) = x (4x + -2x2) = x Solving 4x + -2x2 = x Solving for variable 'x'. Reorder the terms: 4x + -1x + -2x2 = x + -1x Combine like terms: 4x + -1x = 3x 3x + -2x2 = x + -1x Combine like terms: x + -1x = 0 3x + -2x2 = 0 Factor out the Greatest Common Factor (GCF), 'x'. x(3 + -2x) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(3 + -2x)' equal to zero and attempt to solve: Simplifying 3 + -2x = 0 Solving 3 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2x = 0 + -3 -2x = 0 + -3 Combine like terms: 0 + -3 = -3 -2x = -3 Divide each side by '-2'. x = 1.5 Simplifying x = 1.5Solution
x = {0, 1.5}
| 9n-32=24n-1 | | 0.32/0.56=8/x | | 8-8b=8(b-7) | | N+4-3=2 | | f(x)=-2x^2+4x-1 | | -4(5t-4)+7t=5t-7 | | 9(x-4)=37 | | 6(x-.333)=-2(x+23) | | 540-3x=360-2x | | 14x-(x-5)+8=13 | | 320=0.2(1.500+x) | | -(7-4k)=9 | | .9x+8.25=1.5(2+2x) | | 3y=-6x-21 | | -15+5=-2(x+7) | | 6(x-3)+2x=4(2x-1)-22 | | 2(y+7)-7y=-16 | | -2(3t-5)+4t=7t-9 | | (8x^9)^2/3 | | 43+7x= | | 62.1=20+0.5x+0.15(20+0.5x) | | -8r-r-17r+-20r+r+-20=5 | | 2(x+2)=60 | | -106-x+8x=69 | | 0.4a+0.8b=1.2 | | 1-5/4y | | -8r-r-17r-20r+r+-20=5 | | 20-(2x6)8/4 | | 10x-28x= | | 7(4x-4)=28x-28 | | 8X+5+3X+8=180 | | e-0.25x=16 |